2014
DOI: 10.1186/1476-4598-13-174
|View full text |Cite
|
Sign up to set email alerts
|

Influence of secreted frizzled receptor protein 1 (SFRP1) on neoadjuvant chemotherapy in triple negative breast cancer does not rely on WNT signaling

Abstract: BackgroundTriple negative breast cancer (TNBC) is characterized by lack of expression of both estrogen and progesterone receptor as well as lack of overexpression or amplification of HER2. Despite an increased probability of response to chemotherapy, many patients resistant to current chemotherapy regimens suffer from a worse prognosis compared to other breast cancer subtypes. However, molecular determinants of response to chemotherapy specific to TNBC remain largely unknown. Thus, there is a high demand for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 48 publications
3
27
0
Order By: Relevance
“…Anthracyclines have been the backbone of treatment protocols for both diseases for five decades. Downregulated RGS6 and SFRP1 have been correlated with anthracycline resistance in breast and other solid cancers . RGS6 in cancer cells is critical for the cytotoxic action of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracyclines have been the backbone of treatment protocols for both diseases for five decades. Downregulated RGS6 and SFRP1 have been correlated with anthracycline resistance in breast and other solid cancers . RGS6 in cancer cells is critical for the cytotoxic action of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…SFRP1 hypermethylation and downregulation are also associated with poor prognosis in several tumors (34,37,38). Moreover, SFRP1 is associated with tumor chemotherapy, and some antitumor drugs inhibit cell growth through the re-expression of SFRP1 (39)(40)(41). However, emerging evidence has indicated that SFRP1 may also be highly expressed in carcinomas and promote tumor proliferation or migration, such as in basal-like breast cancer (42), gastric cancer (43), and metastatic renal carcinoma (44).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, SFRP1 is a tumor-suppressor in physiological conditions. Furthermore, in triple-negative breast cancer cases, the over-expression of SFRP1 is responsible for an increasing sensitivity to chemotherapy [32]. By its pro-apoptotic effect, SFRP1 is a potential therapeutic tool that should be further investigated.…”
Section: Sfrp1 Expression Is Deregulated In Breast Cancermentioning
confidence: 99%